Clinicopathological correlation of an excised choroidal neovascular membrane in pseudotumour cerebri. Issue 11 (1st November 1997) - Castellarin, Alessandro A; Sugino, Ilene K; Nasir, Ma'an; Zarbin, Marco A
Abstract : AIMS/BACKGROUND: To correlate the histopathology of an excised choroidal neovascular membrane (CNV) with the clinical and angiographic findings in a 32-year-old woman with pseudotumour cerebri and a peripapillary CNV with subfoveal extension. METHODS: The patient's visual acuity was assessed by individuals experienced in low vision refraction and who were not members of the surgical team. The CNV was excised via a conventional three port vitrectomy with subretinal dissection. The excised tissue was studied with light and electron microscopy. Preoperative and serial postoperative fluorescein angiograms (FAs) and fundus photographs were obtained to study the dissection bed. RESULTS: One week after surgery, the FA showed mottled subfoveal choriocapillaris perfusion. Three weeks after surgery, this area showed retinal pigment epithelium (RPE) atrophy clinically, and the FA showed choriocapillaris non-perfusion. Six months after surgery, the area of RPE atrophy and the corresponding area of choriocapillaris non-perfusion had expanded. Histologically, the excised CNV disclosed hyperplastic RPE, fibrovascular tissue, and no choriocapillaris. Fragments of RPE basement were present along the external edge of the specimen. The patient's visual acuity did not improve significantly after surgery. CONCLUSIONS: Choriocapillaris non-perfusion can develop even in young patients following CNV excision. In this particular case, it is believed that choriocapillaris atrophy was caused by incomplete ingrowth of RPE into the dissection bed following RPE removal with CNV excision. As far as is known, this is the first report describing the results of surgery for CNV secondary to papilloedema associated with pseudotumour cerebri.